Conflict and Cultural Heritage : A Moral Analysis of the Challenges of Heritage Protection - Frowe, Helen; Matravers, Derek (J. Paul Getty Trust occasional papers in cultural heritage policy ;, 2020)
In the third issue of the J. Paul Getty Trust Occasional Papers in Cultural Heritage Policy series, authors Helen Frowe and Derek Matravers pivot from the earlier tone of the series in discussing the appropriate response to attacks on cultural heritage with their paper, "Conflict and Cultural Heritage: A Moral Analysis of the Challenges of Heritage Protection." While Frowe and Matravers acknowledge the importance of cultural heritage, they assert that we must more carefully consider the complex moral dimensions--the inevitable serious consequences to human beings--before formulating policy to forcefully protect it. A number of writers and thinkers working on the problem of preserving the world's most treasured monuments, sites, and objects today cite what Frowe and Matravers call extrinsic and intrinsic justifications for the protection of cultural heritage. These are arguments that maintain that protecting heritage will be a key means to achieve other important goals, like the prevention of genocide, or arguments that heritage deserves to be forcefully protected for its own sake. Frowe and Matravers deconstruct both types of justifications, demonstrating a lack of clear evidence for a causal relationship between the destruction of cultural heritage and atrocities like genocide and arguing that the defense of heritage must not be treated with the same weight or urgency, or according to the same international policies, as the defense of human lives. By calling for expanded theory and empirical data and the consideration of morality in the crafting of international policy vis-à-vis cultural heritage protection, Frowe and Matravers present a thoughtful critique that enriches this important series and adds to the ongoing dialogue in the field.